2015
DOI: 10.1186/s40644-015-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Trans-arterial chemoembolization and external beam radiation therapy for treatment of hepatocellular carcinoma with a tumor thrombus in the inferior vena cava and right atrium

Abstract: BackgroundHepatocellular carcinoma (HCC) with a tumor thrombus in the inferior vena cava (IVC) and right atrium (RA) rarely occurs and is usually associated with extremely poor prognosis, we carried out this study to evaluate the efficacy and safety of a combination of trans-arterial chemoembolization (TACE) and external beam radiation therapy (EBRT) in the treatment of HCC with a tumor thrombus in the IVC and RA.MethodsFrom September 2005 to September 2008, 11 cases of HCC with a tumor thrombus in the IVC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 18 publications
(18 reference statements)
1
43
0
Order By: Relevance
“…In total 53 articles were collected , including 5 (9.4%) retrospective studies [3,11,23,50,53], 4 (7.5%) case series [1,21,43,49], and 44 (83.0%) case reports [2, 4-10, 12-20, 22, 24-42, 44-48, 51, 52], with 187 patients involved. Even though cohort studies, case-control studies and case series are considered to form a hierarchy of increasing risk of bias, these studies reflected closely a routine practice or the usual setting where the intervention would be implemented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total 53 articles were collected , including 5 (9.4%) retrospective studies [3,11,23,50,53], 4 (7.5%) case series [1,21,43,49], and 44 (83.0%) case reports [2, 4-10, 12-20, 22, 24-42, 44-48, 51, 52], with 187 patients involved. Even though cohort studies, case-control studies and case series are considered to form a hierarchy of increasing risk of bias, these studies reflected closely a routine practice or the usual setting where the intervention would be implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [3] reported the median survival time of such patients was 4.6 months. Duan et al [11] retrospectively observed 11 cases of HCC with IVC/RA tumor thrombus treated with a combination of TACE and external beam radiation therapy and noted that all patients died of disease progression, and the median survival time was 21 months. The clinical effects of TACE in the treatment of HCC with IVC/RA tumor thrombus were heterogeneous and warrant further observations [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors are aware of a selection bias. Hepatitis B antigen positive [10, 13, 21, 23, 32-34, 46, 47, 50] 33 (30.6) Chronic hepatitis B [8,11,12,15,17,25,44] 17 (15.7)…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, treatment options include TACE, SIRT, or local ablative techniques or systemic treatment with multi-kinase or checkpoint inhibitors [24]. While some reports have evaluated the efficacy of interventional methods in patients with HCC and CATT [25,26], the impact of systemic treatments is poorly described so far.…”
Section: Discussionmentioning
confidence: 99%